DAMPAK NEGATIF IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PROSES PEMBELAJARAN PADA SISWA SEKOLAH DASAR - Adinda Aulia Bestari; Adrias, Adrias; Aissy Putri Zulkarnaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Independent Curriculum takes a different approach from the previous curriculum, particularly in its assessment system, which focuses more on character building rather than students’ academic achievement The automatic grade promotion policy raises concerns about learning quality, as students advance to the next grade level even if they have not yet mastered essential skills. This study seeks to assess the negative impacts of implementing the Independent Curriculum, especially regarding academic gaps and learning effectiveness in elementary schools. By employing a qualitative method with an interpretative descriptive framework, this research aims to explore teachers’ experiences and perspectives in applying the Independent Curriculum. This method allows for a deeper investigation of challenges and policy effects from educators’ viewpoints, particulary in relation to academic disparities and learning efficiency. Moreover, the substitution of the National Examination with Askomi Suka is seen as less effective as a final student assessment tool, as this system not only diminishes academic competitiveness but also hampers the equal attainment of competencies. Teachers also encounter various obstacles in implementing project-bases learning and maintaining flexible teaching methods, which have yet to be executed effectively.